The Role of Ecotourism in Improving the Economy of the Batu Katak Village Community, North Sumatera Province - Ikhlas RAMADHAN; Valentina Lumban GAOL; Windi MIRANDA (Journal of Tourism Economics and Policy, 2023)
Ecotourism is environment and community-based tourism that prioritizes the principles of sustainability and provides benefits to local communities. One of the benefits that can be provided by ecotourism is increased employment opportunities for local people. The purpose of this study is to analyze the role of ecotourism in the economy of the people of Batu Katak Village, Bahorok District, Langkat Regency. The qualitative research method used aims to understand in depth the influence of ecotourism on the economic situation of the community. Data collection was carried out through a triangulation process (observations, depth interviews, and documentation studies). The results of the study indicate that the existence of ecotourism activities in Batu Katak Village plays an important role in the survival of the community, both as the main source of income and as an additional source of income. Additionally, ecotourism activities have both a direct and indirect impact on the community's revenue. It is believed that this research will help village leaders implement ecotourism initiatives to boost the local economy.